A cross-sectional study of the availability and pharmacist's knowledge of nano-pharmaceutical drugs in Palestinian hospitals - Mohyeddin Assali; Ali Shakaa; Sabaa Abu-Hejleh; Reham Abu-Omar; Nareman Karajeh; Nawal Ajory; Saed Zyoud; Waleed Sweileh (BMC, 2018)
Abstract Background Nanomedicine is the medical application of nanomaterials that may have an infinite size with the range less than 100 nm. This science has provided solutions to many of the current limitations in the diagnosis and treatment of diseases. Therefore, the pharmacist's knowledge and awareness of nano-pharmaceutical drugs will increase their availability in the market, and will improve the patient's compliance to their drug therapy. This study aimed to determine the availability of nano-pharmaceutical drugs in Palestinian hospitals and evaluate the extent of pharmacist's knowledge about them. Methods A cross-sectional study design questionnaire was used to determine the availability of nano-pharmaceutical drugs based on the database of the ministry of health in the Palestinian hospitals (governmental, private and non- governmental organizations). Moreover, the knowledge of these nano-pharmaceutical drugs among pharmacists working in Palestinian hospitals was assessed based on developed questionnaire from the literature of the pharmaceutical formulations and nano-formulations. The variables were analyzed using Statistical Package for Social Sciences (SPSS 22). Result Fifty six pharmacists from 27 hospitals in the West bank completed the survey. The results regarding the availability of nano-pharmaceutical drugs indicated only eight available in hospitals with a frequency range 0-39.3%. Moreover, pharmacist's knowledge in the pharmaceutical formulations was better than that in nano-formulations. Conclusions The availability of nano-pharmaceutical drugs in Palestinian hospitals was not adequate due to the lack of various nano-pharmaceutical drugs. The knowledge among pharmacists regarding nano-pharmaceutical drugs should be improved by providing courses in nanomedicine during the undergraduate pharmacy programs.